2017
DOI: 10.1186/s12864-017-4057-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of bacterial small RNAs in the RsmA (CsrA) and ToxT pathways: a machine learning approach

Abstract: BackgroundSmall RNAs (sRNAs) constitute an important class of post-transcriptional regulators that control critical cellular processes in bacteria. Recent research using high-throughput transcriptomic approaches has led to a dramatic increase in the discovery of bacterial sRNAs. However, it is generally believed that the currently identified sRNAs constitute a limited subset of the bacterial sRNA repertoire. In several cases, sRNAs belonging to a specific class are already known and the challenge is to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Importantly, combined the InvenireSRNA prediction (Fakhry et al, 2017), Rfam alignment and secondary structure analysis, we identified two putative Csr A-related s R NAs (named CsrR1 and CsrR2) from the 549 sRNAs of A. dieselolei (Figures 4A, 7A to 7C, Tables S10 and S18), which may sequester the CsrA regulator and therefore indirectly involve in the alkane metabolism. CsrR1 originated from the 5’UTR of hfq (B5T_00774).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, combined the InvenireSRNA prediction (Fakhry et al, 2017), Rfam alignment and secondary structure analysis, we identified two putative Csr A-related s R NAs (named CsrR1 and CsrR2) from the 549 sRNAs of A. dieselolei (Figures 4A, 7A to 7C, Tables S10 and S18), which may sequester the CsrA regulator and therefore indirectly involve in the alkane metabolism. CsrR1 originated from the 5’UTR of hfq (B5T_00774).…”
Section: Resultsmentioning
confidence: 99%
“…CsrA-related sRNAs were identified with the assistance of the R package “InvenireSRNA”, which integrated sequence- and structure-based features to train machine-learning models for detecting the bacterial sRNAs in the CsrA pathway (Fakhry et al, 2017). All the sRNA candidates and the extracted intergenic sequences of the whole genome were scanned using the InvenireSRNA to discover all the possible CsrA-related sRNAs in A. dieselolei .…”
Section: Methodsmentioning
confidence: 99%
“…CsrA from C. jejuni is longer (75 amino acids), and its activity is modulated by FliW ( Dugar et al, 2016 ; Radomska et al, 2016 ; Li et al, 2018 ). In contrast, E. coli CsrA is shorter (61 amino acids) ( Figure 1A ) and its activity is regulated by binding to sRNAs ( Jin et al, 2002 ; Thomson et al, 2006 ; Babitzke and Romeo, 2007 ; Fakhry et al, 2017 ; Janssen et al, 2018 ; Potts et al, 2019 ). As the C-terminus of C. jejuni CsrA is longer than the analogous region of CsrA proteins of E. coli and other bacteria, whose activities are regulated by sRNAs rather than by FliW ( Fields and Thompson, 2012 ), and adjacent to the most C-terminal β-strand (β 5 ) that is involved in RNA binding in both E. coli and C. jejuni ( Figure 1A ; Mercante et al, 2006 ; El Abbar et al, 2019 ), we hypothesized that FliW would bind to this region.…”
Section: Resultsmentioning
confidence: 99%
“…The machine-learning-based algorithm InvenireSRNA ( Fakhry et al, 2017 ) is designed to predict sRNAs of the CsrB/C family. To gauge how RrA, B, F rank in this algorithm compared to other E. coli non-coding RNAs, we provided the algorithm with a total of 2902 sequences, including all annotated E. coli sRNA sequences, the 22 TLR sequences, all sequences identified as CsrA-binding peaks from CLIP-seq data ( Potts et al, 2017 ), and finally all intergenic regions of E. coli shorter than 1,000 bp.…”
Section: Resultsmentioning
confidence: 99%